Epigenetic abnormalities and neuroendocrine differentiation in prostate cancer - G. A. Kovchenko; A. V. Sivkov; L. N. Lyubchenko; A. D. Kaprin (Сибирский онкологический журнал)
Objective. Unlike genetic changes, epigenetic aberrations in prostate cancer can be reversed under the influence of a chemical agent. This fact makes the study of epigenetic changes an important object as potential therapeutic targets. Material and methods. PubMed, Medline, eLibrary.ru databases were analyzed for the keywords: epigenetic prostate cancer, lineage plasticity, neuroendocrine differentiation. For this literature review, 84 relevant publications were selected. The review included studies from 1982 to 2024. Results. The most widely studied epigenetic mutations are DNA hypo- and hypermethylation, histone variability (methylation and acetylation), and neuroendocrine differentiation. Conclusion. The study of the genomic landscape can reveal new opportunities for improving the diagnosis and therapy of castration-resistant prostate cancer (CRPC), which is a potentially lethal form of the disease. It is important not only to search for new biomarkers to identify genetic disorders, but also to study the optimal therapy for advanced prostate cancer.